2011
DOI: 10.1021/ma200986d
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects in Ionic Pairing and Polyelectrolyte Interdiffusion within Multilayered Films: A Neutron Reflectometry Study

Abstract: Using a series of polycations synthesized by atom transfer radical polymerization (ATRP), we investigate the effects of the polymer charge density and hydrophobicity on salt-induced interdiffusion of polymer layers within polyelectrolyte multilayer (PEM) films. Polycations with two distinct hydrophobicities and various quaternization degrees (QPDMA and QPDEA) were derived from parent polymers of matched molecular weightspoly(2-(dimethylamino)ethyl methacrylate) (PDMA) and poly(2-(diethylamino)ethyl methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
94
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 63 publications
5
94
0
2
Order By: Relevance
“…/s for chitosan of roughly the same molecular weight is larger but well within the range of other exponentially growing polymer systems previously studied. In addition, the diffusion coefficient we report would be higher than the diffusion coefficient of chitosan in a pure film of chitosan/heparin, as Xu et al (30) showed that weaker matrix interactions enable a higher diffusion coefficient. Given that in our study chitosan diffused in a hydrogen-bonded (PAA3/PEO3) matrix with a low interaction strength, as measured by dissolution pH, and did not have an internal structure, as measured by neutron reflectivity (51), it thus would allow for a diffusion coefficient higher than that of the more strongly interacting electrostatic matrix of chitosan and heparin.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…/s for chitosan of roughly the same molecular weight is larger but well within the range of other exponentially growing polymer systems previously studied. In addition, the diffusion coefficient we report would be higher than the diffusion coefficient of chitosan in a pure film of chitosan/heparin, as Xu et al (30) showed that weaker matrix interactions enable a higher diffusion coefficient. Given that in our study chitosan diffused in a hydrogen-bonded (PAA3/PEO3) matrix with a low interaction strength, as measured by dissolution pH, and did not have an internal structure, as measured by neutron reflectivity (51), it thus would allow for a diffusion coefficient higher than that of the more strongly interacting electrostatic matrix of chitosan and heparin.…”
Section: Resultsmentioning
confidence: 57%
“…These techniques include confocal microscopy (23)(24)(25), FRET (26,27), FTIR (28), neutron reflectivity (29)(30)(31), and X-ray reflectometry (32). Confocal microscopy is limited in spatial sensitivity, as films much thicker than the typical PEM thickness (≤500 nm) are required because of a relatively low z-resolution (23)(24)(25).…”
mentioning
confidence: 99%
“…A recent study has shown that steric hindrance reduces the electrostatic interactions of quaternary amines in the case of PDADMAC [44]. Although PDADMAC is a strong polyelectrolyte, its quaternary nitrogen atom encounters greater steric hindrance to interaction with the carboxyl group on PAA, as compared to the tertiary nitrogen atom on PDMAEMA.…”
Section: Resultsmentioning
confidence: 99%
“…For example, salt-induced diffusion of PEs in the direction parallel to the surface was observed with several PEM systems using FRAP, 7,8 while intermixing of polymer layers was studied in different PEM systems using NR. 10,11,12 Because of the inherently anisotropic structure of PEMs, it is reasonable to suggest that chain mobility might be different in directions parallel and perpendicular to the substrate. However, the experiments testing this suggestion, as well as the effect of the proposed anisotropic chain motions on film layering have not up to now been carried out.…”
mentioning
confidence: 99%